PENGARUH PEMBANGUNAN EMBUNG (PENAMPUNGAN AIR) TERHADAP HASIL PANEN PETANI DI DESA PACCEKKE KECAMATAN SOPPENG RIAJA KABUPATEN BARRU - Yusuf Asri; Dalilul Falihin (Social Landscape Journal, 2022)
Moh. Yusuf Asri, 2022. The Effect of Embung (Water Storage) Development on Farmers' Harvests in Pacekke Village, Soppeng Riaja District, Barru Regency. Thesis, Faculty of Social Sciences and Law, Makassar State University. Supervised by Dalilul Falihin and Syarifah Balkis. The research was carried out with the following objectives: 1) To find out the description of the construction of a reservoir (water reservoir) in Pacekke Village, Soppeng Riaja District, Barru Regency. 2) To find out the description of farmers' harvests in Pacekke Village, Soppeng Riaja District, Barru Regency and 3) To find out whether there is any effect of the construction of a reservoir (water reservoir) on farmers' harvests in Pacekke Village, Soppeng Riaja District, Barru Regency. The type of research used is descriptive quantitative. The variables of this study consisted of the construction of reservoirs (water reservoirs) (variable X) and the yield of petahi (variable Y) data collection techniques using observation, questionnaires/questionnaires and documentation. The data analysis technique used is descriptive statistics and inferential analysis. Based on the research, it is known that: 1) The construction of a reservoir (water reservoir) in Pacekke Village, Soppeng Riaja District, Barru Regency is included in the "Very Good" category in terms of the indicators of the benefits of the development of the reservoir in environmental aspects, economic aspects, and social aspects of farmers in Pacekke Village, Soppeng Riaja District. Barru District. 2) The harvest in Pacekke Village, Soppeng Riaja District, Barru Regency is classified as "Good" in terms of market quality, cooking quality, and taste quality and 3) There is a positive and significant influence as evidenced by research and the correlation results are 0.655 which is in "Strong" category. Thus H0 is rejected and H1 is accepted, that is, there is an effect of the construction of a reservoir (water reservoir) on farmers' harvests in Pacekke Village, Soppeng Riaja District, Barru Regency